Developing The Quality Of Islamic Corporate Culture On Islamic Bank In Indonesia - Muhammad Iqbal Fasa (JES (Jurnal Ekonomi Syariah), 2018)
Financial institutions and contemporary business today have been transformed into a sharia-based financial institution and business. However, this change of a new transformation is done systemically by system and not implemented by culture. Thus, despite the growth of Islamic bank is so high, polemics is increasingly unsettled. Based on this, the necessary of transformation of corporate culture has to change based on Islamic values to create sustainable development and competitive advantage. This paper attempts to offer relevant ideas based on Islamic corporate culture. At the end of this paper, the author offers the characteristics of Islamic corporate culture, corporate culture in Islamic bank in Indonesia, and the development of quality of Islamic corporate culture on Islamic bank in Indonesia. This paper concludes that Islamic corporate culture has a major role in increasing employee motivation, employee work ethic, job satisfaction, employee's prestigious behavior and employee performance. Thus, it is important for Islamic banks to develop the quality of corporate culture based on Islamic values. Keywords: Islamic Corporate Culture, Islamic Bank, Sustainable Development